Lessons from rare diseases of cartilage and bone. (June 2015) - Gallagher, James A; Ranganath, Lakshminarayan R; Boyde, Alan
Highlights: Studying rare syndromes helps elucidate disease mechanisms of more common disorders. Lessons from rare bone diseases have contributed to the development of osteoanabolic therapies. Osteoarthritis (OA) is a common disease with currently no effective therapies. Investigation of rare cartilage syndromes is identifying new targets in OA. HDMPs identified in AKU and then OA constitute a new mechanism of joint destruction. Abstract : Studying severe phenotypes of rare syndromes can elucidate disease mechanisms of more common disorders and identify potential therapeutic targets. Lessons from rare bone diseases contributed to the development of the most successful class of bone active agents, the bisphosphonates. More recent research on rare bone diseases has helped elucidate key pathways and identify new targets in bone resorption and bone formation including cathepsin K and sclerostin, for which drugs are now in clinical trials. By contrast, there has been much less focus on rare cartilage diseases and osteoarthritis (OA) remains a common disease with no effective therapy. Investigation of rare cartilage syndromes is identifying new potential targets in OA including GDF5 and lubricin. Research on the arthropathy of the ultra-rare disease alkaptonuria has identified several new features of the OA phenotype, including high density mineralized protrusions (HDMPs) which constitute a newly identified mechanism of joint destruction.